2019
DOI: 10.31807/tjwsm.492214
|View full text |Cite
|
Sign up to set email alerts
|

Common Diatoms of Phytobenthos in Gediz River Basin

Abstract: Diatoms (important representatives of phytobenthos) are ecologically significant quality elements for rivers and lakes according to the EU Water Framework Directive (2000/60/EC). We aimed to investigate common diatoms of Gediz River Basin within the scope of the studies for preparation of Gediz River Basin Management Plan. Samples were collected from epilithon and epipelon substrates of 17 rivers, 2 lakes (Gölcük and Marmara) and 4 dams (Demirköprü, Küçükler, Buldan, Afşar) from November 2017 to April 2018. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Although the commonly used parameters are various basic ecological variables such as water temperature, pH, dissolved oxygen, and nutrients, the excessive increase or decrease of some biological groups depending on these variables are observed. In particular, species composition and the abundance status of diatoms change depending on these variables and are used as an important indicator in determining the trophic status of lakes (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Although the commonly used parameters are various basic ecological variables such as water temperature, pH, dissolved oxygen, and nutrients, the excessive increase or decrease of some biological groups depending on these variables are observed. In particular, species composition and the abundance status of diatoms change depending on these variables and are used as an important indicator in determining the trophic status of lakes (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Demir et al (2017) reported diatom composition of Lake Eber and the streams in Akarçay River Basin, while analysed the distribution of diatoms in streams and reservoirs of Küçük Menderes River. Benthic diatom community of streams, lakes and reservoirs of Gediz River Basin was also studied by Solak et al (2019). Unlike the other 24 river basins in Turkey, there is no data on benthic diatom composition in the lakes and streams of Burdur River Basin.…”
Section: Introductionmentioning
confidence: 99%